Studies in law, politics, and society. Vol. 50 - Sarat, Austin (Bingley, UK : Emerald, 2009)
This volume of "Studies in Law, Politics, and Society" brings together research on law's cultural life and on institutions and actors who translate interests, preferences, and values into legal policy. It offers perspectives from an interdisciplinary and international community and contains contributions from scholars of theology, political science, criminology, bio-ethics, and law in the United States, Israel, and Canada.
Includes bibliographical references.
Description based on print version record.
Keywords: Political sociology -- Research; Political sociology -- Research -- United States; Sociological jurisprudence -- Research -- United States; Sociology -- Research -- United States; Law & society; Courts & procedure; Law -- Trial Practice